Theoretical Approach On The Growth Rate Of Solidified Metal Interface - D. Prayitno, D. Prayitno; Esah, Hamzah; Mohd. Ghazali, Mohd. Zulkifli; Clegg, A. J. (Penerbit UTM Press, 2001)
When nucleation is completed, the solidification process will continue with nucleus growth. Increasing the growth rate will reduce the grain size of metal. Thus the study on the casting parameters which have an effect on the growth rate should be carried out in order to improve the mechanical properties of the metal. This work thus proposes an equation of growth rate of solidified metal interface in the molten state which is poured from a moving tundish into an inclined mould. The proposed equation can be practically applied and the parameters can be experimentally determined.